2023
DOI: 10.3389/fmed.2022.1045060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ABO blood groups and RH-factor on COVID-19 transmission, course and outcome: A review

Abstract: ABO and Rh blood grouping systems are two of the non-modifiable risk factors that play an important role in the susceptibility, severity and outcomes of COVID-19 infection. This review explores these associations all over the world, in an attempt to conclude a clear idea for future reference in clinical practice. In the present review, a link has been drawn between blood groups and COVID-19 transmission, course and prognosis, as literature suggests that blood group O plays a protective role against the infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…19 In an interesting study done in Saudi Arabia by Hindawi and colleagues, it was found that those with blood group B had the highest risk of contracting the virus compared to people with blood groups A and AB. 46 In contrast to many other investigations, [47][48][49] these authors did not find a connection between the disease and Rh factors. To further substantiate their findings, the authors recommended a bigger sample size.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…19 In an interesting study done in Saudi Arabia by Hindawi and colleagues, it was found that those with blood group B had the highest risk of contracting the virus compared to people with blood groups A and AB. 46 In contrast to many other investigations, [47][48][49] these authors did not find a connection between the disease and Rh factors. To further substantiate their findings, the authors recommended a bigger sample size.…”
Section: Discussioncontrasting
confidence: 77%
“…Old age, chronic diseases, gender, 19 immunocompromised condition, blood type A (Rh +ve), and other factors are known risk factors for contracting and later developing severe COVID-19. 19 See the studies by Shibeeb and Khan, 20 Abuawwad et al, 21 Turhan et al, 22 and Hafez et al 23 for comprehensive recent reviews on the relationship between the ABO blood system and the Rh factor and their association with COVID-19 infection, susceptibility, and severity. Although the initial virus that caused the first-ever SARS in Hong Kong in March 2003 19 is no longer a concern, the known characteristics of the current SARS-CoV-2 do not appear to disappear quickly, and many countries are now experiencing the second wave of the outbreak.…”
Section: Association Of Abo Blood Types and Clinical Variables With C...mentioning
confidence: 99%
“…Initial reports from the onset of the pandemic indicated a link between COVID-19 severity and ABO blood groups [39], with subsequent research works reporting similar findings. In particular, blood group A patients were shown to exhibit both increased susceptibility to SARS-CoV-2 infection [38,[40][41][42][43][44][45][46][47][48][49][50][51] and increased illness severity [42,47,48,[52][53][54]. Increased infection susceptibility has also been reported for individuals of blood group AB [46,50], as well as for those of blood group B in addition to blood group A [47], while one study reported reduced susceptibility for individuals of the AB blood group [43].…”
Section: Abo Blood Groups and Secretor Status In Relation To Covid-19...mentioning
confidence: 99%
“…COVID-19 has a duration of incubation ranging from one to 14 days, with symptoms commonly appearing within three to seven days. There were numerous instances when the COVID-19 infection developed over 14 days to show any symptoms [7][8][9][10][11]. The International Society for the Study of Blood Transfusion (ISBT) has identified 34 distinct blood group types.…”
Section: Introductionmentioning
confidence: 99%
“…The comprehension of the diverse groups of blood subtypes and their association with COVID-19 has the potential to contribute to the successful treatment and therapeutic approaches for the condition. Abuawwad et al [9] observed that the subjects with the Rh+ type of blood had more likelihood of testing positive for SARS-CoV- [12]. Elderly individuals seem to be more vulnerable to the virus, with 75% of confirmed cases occurring in individuals aged 50 and above.…”
Section: Introductionmentioning
confidence: 99%